Hugo Jamioy Juagibioy, Esta geografía me está diciendo (Medellín, Confama-Metro de Medellín, 2023, 142 pp. ISBN 978-628-7637-36-8) (Altre Modernità, 2025)
Hugo Jamioy Juagibioy, Esta geografía me está diciendo(Medellín, Confama-Metro de Medellín, 2023, 142 pp. ISBN 978-628-7637-36-8)